Análise teórica de um concentrador parabólico composto evacuado de baixo custo submetido ao efeito estufa - Silva, Felipe Vilar da (2021)
The present work performs a study for the theoretical analysis of a low-cost evacuated and greenhouse-effect composite parabolic concentrator. The main objective is to evaluate the achievement of high temperatures and establish conditions for higher levels of exergy, with the use of solar energy using the compound parabolic concentrator (CPC). The main advantage of using CPC is the applicability of different solar radiation concentration factors without the need to track the sun throughout the day. This dramatically reduces the cost of the system by eliminating the solar tracking device. For the development, a fabrication methodology is proposed and analyzed, with an innovative concept, which allows the fabrication at a relatively low cost, making it possible for its application, essentially, in needy communities for the most diverse applications. To increase the efficiency of the CPC, it is also proposed to evacuate the air inside the gutter, together with the use of a greenhouse effect with a glass cover. The results show increased efficiency compared to the nonevacuated manifold and the possibility of reaching an efficiency close to 50% for a working fluid temperature above 100 degrees.